THE INFLUENCE OF CASH TURNOVER AND INVENTORY TURNOVER ON PROFITABILITY WITH COMPANY SIZE AS A MODERATING VARIABLE - Agus Prayitno; Ngatno Ngatno; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2025)
This research aims to determine the effect of cash turnover and inventory turnover on profitability, with company size as a moderating variable, a study on Textile and Garment Sub-Sector Companies during the period of 2018 – 2023. The sampling method in this study used purposive sampling technique, resulting in 12 selected companies from 22 companies in the Textile and Garment sector listed on the Indonesia Stock Exchange. (BEI). This research uses quantitative data. The data source in this research is secondary data. The analysis methods used linear regression. The results of this study indicate that, partially, Cash Turnover has a negative and significant effect on profitability, while Inventory Turnover has a positive and significant effect on profitability in companies within the Textile and Garment Sub-Sector during the period of 2018 – 2019. Furthermore, simultaneously, Cash Turnover and Inventory Turnover have a positive and significant effect on profitability in companies within the Textile and Garment Sub-Sector during the period of 2018 – 2019. Additionally, the moderation regression analysis revealed that company size does not moderate the effect of cash turnover on profitability, nor does it moderate the effect of inventory turnover on profitability.